2017
DOI: 10.1002/ange.201706974
|View full text |Cite
|
Sign up to set email alerts
|

Flavylium Polymethine Fluorophores for Near‐ and Shortwave Infrared Imaging

Abstract: Bright fluorophores in the near‐infrared and shortwave infrared (SWIR) regions of the electromagnetic spectrum are essential for optical imaging in vivo. In this work, we utilized a 7‐dimethylamino flavylium heterocycle to construct a panel of novel red‐shifted polymethine dyes, with emission wavelengths from 680 to 1045 nm. Photophysical characterization revealed that the 1‐ and 3‐methine dyes display enhanced photostability and the 5‐ and 7‐methine dyes exhibit exceptional brightness for their respective spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…Increasing the quantum yield, functionality, and biocompatibility of SWIR fluorophores is an active focus of emerging research studies (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Significancementioning
confidence: 99%
“…Increasing the quantum yield, functionality, and biocompatibility of SWIR fluorophores is an active focus of emerging research studies (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Significancementioning
confidence: 99%
“…With recent progress in InGaAs fabrication, the cost of SWIR cameras has steadily declined, while camera sensitivity and resolution have increased. Moreover, a wide variety of biologically compatible SWIR emitters have emerged, including organic dyes with peak emission in the SWIR (7)(8)(9)(10), carbon nanotubes (11,12), quantum dots (13)(14)(15), rare-earth−doped nanocomposites (16), and gold nanoparticles (17). More recently, it was also shown that NIR dyes, which are commercially available and approved for clinical use, can be used for many SWIR imaging applications (18).…”
mentioning
confidence: 99%
“…It is obvious that the catalogue of tested organic NIR sensitizers for upconverters is very limited. Other candidate dyes with absorptions abovẽ 750 nm are croconic dyes, organic metal complexes, donor-acceptor charge transfer chromophores or extended π-conjugated chromophores, but it should be mentioned that some of these dyes are difficult to synthesize, have poor solubility, or low molar absorptivity [65][66][67][68][69][70]. An interesting class of NIR dyes for further investigation is cyanines.…”
Section: Challenges and Outlookmentioning
confidence: 99%